Upaya Meningkatkan Keterampilan Berbicara Siswa Dengan Menggunakan Metode Mind Mapping Pada Siswa Kelas V SDN No. 18 Bababulo Kabupaten Majene - Sulpardina Rifai; Muhammad Akhir; Abdan Syakur (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aims to improve students' speaking skills through the mind mapping method for fifth grade students at SDN NO. 18 Bababulo Majene Regency. The subjects used in this research were 15 students. This research procedure consists of 4 stages per cycle, namely planning, implementing actions, observing and reflecting. The indicator of learning outcomes in this research is increasing speaking skills. The data collection was carried out using observation, evaluation and documentation techniques. The results of this study showed that there was an increase in student activity, namely in the first cycle 61.9%, an increase in the second cycle to 82.4%. There was an increase in learning outcomes from cycle I, obtaining an average score of 61.06% with learning completeness of 53.33%. In cycle II the average score was 75.4% with learning completeness 86.67%. Thus, it can be concluded that the use of the mind mapping method can improve speaking skills in class V students at SDN NO. 18 Bababulo Majene Regency.